STRATEGI PENINGKATAN IMPLEMENTASI PENATAUSAHAAN ASET TETAP PADA PEMERINTAH KOTA BOGOR - Aprianti, Radna Rika; Rachmina, Dwi (Jurnal Manajemen Pembangunan Daerah, 2018)
The objectives of this research were to analyze the internal and external factor of fixed assets administration at Bogor City government, and to formulate strategies for improving the implementation of fixed assets administrations at Bogor City Government. The method used in this research is analysis of IFE, EFE, SWOT, and QSPM. The results showed in the administration of fixed asset at Bogor City Government, the opportunity for BMD management apparatus for their human resource development be the main strength; BMD management apparatus do not focus on their own duties is main weakness; the central government regulations that support the administration of fixed assets and regular assessments by Audit Board of Indonesia (BPK) is opportunity; and the lack of orderliness of housing developers in the delivery of social facility and public facilities is threat. The priority strategy for the improvement of the implementation of fixed asset management in the Government of Bogor City that is the strategy of increasing the supporting factors of the performance of the BMD management apparatus and the strategy of improving the quality of the BMD management apparatus.Keywords: fixed assets, IE, SWOT, QSPM